2016
DOI: 10.5959/eimj.v8i2.437
|View full text |Cite
|
Sign up to set email alerts
|

Validity Evidence of a Multiple Mini Interview for Selection of Medical Students: Universiti Sains Malaysia Experience

Abstract: Introduction: Student selection is important for selecting the best candidates into medical courses. The Multiple Mini Interview (MMI) is a valid selection tool for the task. The School of Medical Sciences (SMS), Universiti Sains Malaysia (USM) has employed MMI as a medical admission tool to select potential candidates into its medical program. Objective: This paper described the implementation of the MMI and reported the preliminary evaluation data on its validity evidence. Method: A 9-station MMI (with 5 man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Table 1 shows 49 articles reported evidence to support the content of MMI, while Table 2 shows that 40 articles support the internal structure2, 4, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47; 37 articles support the response process2, 5, 6, 11, 12, 14, 18, 19, 20, 23, 25, 26, 27, 28, 30, 31, 33, 37, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62; 21 articles support the relation to other variables,4, 15, 16, 17, 21, 24, 25, 29, 38, 39, 40, 44,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 shows 49 articles reported evidence to support the content of MMI, while Table 2 shows that 40 articles support the internal structure2, 4, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47; 37 articles support the response process2, 5, 6, 11, 12, 14, 18, 19, 20, 23, 25, 26, 27, 28, 30, 31, 33, 37, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62; 21 articles support the relation to other variables,4, 15, 16, 17, 21, 24, 25, 29, 38, 39, 40, 44,…”
Section: Resultsmentioning
confidence: 99%
“…Internal structure . Six studies reported an MMI internal consistency level (Cronbach's alpha) of less than 0.7,19, 22, 23, 26, 28, 38 whereas 18 articles reported at least 0.70 11, 12, 13, 16, 18, 19, 21, 22, 23, 24, 26, 31, 32, 34, 37, 43, 44, 47. The lowest and highest levels of internal consistency were 0.54 38 and 0.98, 13 respectively (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The candidates were assessed on language proficiency, general conduct, critical thinking, ethical awareness, communication skills, knowledge of the healthcare system, and standard interview questions. 20 Ranked on their scores, the top 150 candidates were recommended for the medical program.…”
Section: Methodsmentioning
confidence: 99%
“…24 Each statement was rated using a 4-point Likert scale ranging from 0 (did not apply to me at all) to 3 (applied to me very much). Based on the DASS manual for student samples 22 , 23 , 24 ; 1) stress level is categorized as normal (0–14), mild, 15 , 16 , 17 , 18 moderate, 19 , 20 , 21 , 22 , 23 , 24 , 25 severe, 16 , 26 , 27 , 28 , 29 , 30 , 31 , 32 and extremely severe (34 and above); 2) Anxiety level is categorized as normal (0–7), mild, 8 , 9 moderate, 10 , 11 , 12 , 13 , 14 severe 15 , 16 , 17 , 18 , 19 and extremely severe (20 and above); and 3) Depression level is categorized as normal (0–9), mild, 10 , 11 , 12 , 13 moderate, 14 , 15 , 16 , 17 , 18 , 19 , 20 severe 21 , 22 , 23 , 24 , 25 , 26 , 27 and extremely severe (28 and above). Any scores of moderate to extremely severe levels were considered as unfavourable stress, anxiety, and depression.…”
Section: Methodsmentioning
confidence: 99%